Function of Train Traction Department and Railway Vehicles in Logistic Centres - Kolar, Velimir; Magličić, Denis; Kaužljar, Dražen (Promet - Traffic&Transportation)
The increasing globalization has spread the production locationsto every part of the world thus increasing even more therole of transport in determining the price and quality of a product.Therefore, the producers and carriers join together moreand more frequently through the supply chains. Railway carriershave a very significant role in supply chains, both throughorganization of transport and forming the trains as final products,and through forming the logistic centres. Logistic centresare the starting and the final railway stations but also the meetingpoints of the national carrier with other carriers (sea, road,river as well as other railway carriers) and they also represent informationcentres. For the quality of service at logistic centres, itis important to have well organized operation of train traction.In order to keep up the regulmity of trains and the quality oftransport at logistic centres, among other things, it is necessaryto provide an optimal number of locomotives and to providethe technical inspection place. Special attention should be paidto the organization of work peiformed by the engine staff At logisticcentres it is possible to organize high-quality technical inspectionof wagons thus increasing the traffic safety.